Actividad antiinflamatoria in vitro de corteza de Maytenus macrocarpa (Ruiz & Pav.) Briq. y hojas de Justicia spicigera Schltdl sobre eritrocitos plasmáticos - Rengifo Linari, Lesly Fernanda (2022)
The objective of this research work was to determine the in vitro anti-inflammatory activity of ethanolic extract from the bark of Maytenus macrocarpa (Ruiz &Pav.) Briq. "chuchuhuasi" and Justicia spicigera Schltdl "insulin" leaves by the method of stabilization of the red blood cell membrane, in dilutions of 10, 100, 1000 and 4000 ug / mL of both extracts and hydrocortisone (reference drug) where it was used NaCl 0.9% as dilution medium. The results for M. macrocarpa were 25.48% at a concentration of 10 ug / mL; 40.25% at 100 ug / mL; 62.64% at 1000 ug / mL and 64.46% at 4000 ug / mL; for J. spicigera 20.12% at a concentration of 10 ug / mL; 33.56% at 100 ug / mL; 52.28% at 1000 ug / mL and 55.22% at 4000 ug / mL; while Hydrocortisone 29.38% at a concentration of 10 ug / mL; 44.56% at 100 ug / mL; 74.53% at 1000 ug / mL and 82.65% at 4000 ug / mL, significant differences were found between the averages of protection percentages and concentrations in all the groups evaluated. The values of IC50 = 325.06 ug for M. macrocarpa bark, leaves of J. spicigera, an IC50 = 1201.91 ug and IC50 = 109.96 ug for Hydrocortisone, allowed to conclude that the latter is the one with the best anti-inflammatory activity in vitro.